TECTONIC STRAIN AND SEISMIC HAZARD ESTIMATION IN SUNDA STRAIT BASED ON GPS OBSERVATION DATA - Marta Nugraha Hidayat; Irwan Meilano; Irwan Gumilar (Widyariset, 2012)
Sunda strait has a relatively high seismic activity. The high seismic activity was caused by the seismic zoneat that region, including the faults zone. Based on the high seismic activity in the Sunda Strait, it is necessary to doresearch about the strain that occurred in the Sunda Strait region to determine the tectonic activity in that area andits seismic hazard. To observe the tectonic activity in the Sunda Strait, GPS observations were made periodicallywith static differential method at the observation points located in the Sunda Strait region. Based on the strainanalysis, the southwestern part of the Sunda Strait tend to experience compression and the northeastern part tendto experience extention. Sunda Strait had a relatively high seismic hazard with maximum PGA 0,47 g.